Does graduate students' satisfaction with research laboratory affect their anxiety? Findings from a cross-sectional study at a Japanese university - Zheng, Li; Deng, Weida (Frontiers in Psychology, 2025)
This study investigates the relationship between graduate students' satisfaction with their research laboratories and their anxiety levels, using 2017 survey data from a Japanese university. Through correlation analysis and Structural Equation Modeling (SEM), this study examined how factors such as laboratory satisfaction, research outcome satisfaction, financial burden, and anxiety are interconnected. The findings reveal three key insights. First, graduate students report the highest levels of anxiety related to future prospects, employment, and economic conditions, and they are most likely to seek advice from parents or partners when experiencing anxiety. Second, satisfaction with the research laboratory significantly reduces anxiety, with the guidance methods of supervisors, interpersonal relationships, and research funding being the most influential factors. Satisfaction with research outcomes also plays a notable mediating role in this relationship. Third, seeking anxiety counseling is associated with increased anxiety levels, particularly when advice is sought from peers. These findings underscore the importance of the research laboratory environment in shaping graduate students' psychological wellbeing and provide a framework for understanding the mechanisms underlying anxiety development. This study highlights the need for universities to address laboratory dynamics and support systems to mitigate graduate student anxiety.